2021
DOI: 10.1038/s41598-021-81939-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bone marrow stem and progenitor cell seeding on urinary bladder tissue regeneration

Abstract: Complications associated with urinary bladder augmentation provide the motivation to delineate alternative bladder tissue regenerative engineering strategies. We describe the results of varying the proportion of bone marrow (BM) mesenchymal stem cells (MSCs) to CD34 + hematopoietic stem/progenitor cells (HSPCs) co-seeded onto synthetic POC [poly(1,8 octamethylene citrate)] or small intestinal submucosa (SIS) scaffolds and their contribution to bladder tissue regeneration. Human BM MSCs and CD34 + HSPCs were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…As anticipated, augmentations with cell-seeded scaffolds in this study showed a significant increase in revascularization and nerve regeneration compared to that of the cell-free scaffolds, and the extent of vascular and nerve regeneration is analogous to previous publications. 22,29 Furthermore, the presence of microgrooves appeared to induce ingrowth of nerves in the unseeded Microgrooved group. Approximately 60% of the smooth group had observed nerve regeneration compared to about 90% of the Microgrooved group.…”
Section: Discussionmentioning
confidence: 95%
“…As anticipated, augmentations with cell-seeded scaffolds in this study showed a significant increase in revascularization and nerve regeneration compared to that of the cell-free scaffolds, and the extent of vascular and nerve regeneration is analogous to previous publications. 22,29 Furthermore, the presence of microgrooves appeared to induce ingrowth of nerves in the unseeded Microgrooved group. Approximately 60% of the smooth group had observed nerve regeneration compared to about 90% of the Microgrooved group.…”
Section: Discussionmentioning
confidence: 95%
“…In a rat urinary bladder augmentation model, MSCs and hematopoietic stem/progenitor cells were seeded onto different scaffolds and were transplanted into rats. This treatment promoted bladder tissue regeneration, partially through the formation of blood vessels [88]. The application of an ointment based on MSC's secretome had an accelerating effect on skin wound healing in mice [89].…”
Section: Mscs In Other Diseasesmentioning
confidence: 98%
“…Drew et al observed neovascularization in the presence of exogenous Vascular Endothelial Growth Factor (VEGF) ( Dew et al, 2016 ). However, another study revealed that in bladder tissue regeneration, poly (octamethylene citrate) (POC) composites outperformed small intestinal submucosa (SIS) scaffolds in tissue vascularization, while POC scaffolds lack any exogenous growth factor ( Bury et al, 2021 ). Stem cells are considered beneficial in angiogenesis induction, as they can differentiate into endothelial cells or secrete various growth factors.…”
Section: Pre-application Processingmentioning
confidence: 99%